Microbiological and Physico-chemical Quality Properties of Wheat Varieties in Turkey - ALP, AYDIN; VURAL, AYDIN; EMIN ERKAN, MEHMET; YESILMEN, SIMTEN (Asian Journal of Chemistry, 2010)
In this study, the microbiological and physico-chemical quality properties of 27 different wheat cultivars produced in Turkey were determined. The means total aerob mesophilic bacteria (TAMB), coliforms, Bacillus cereus, Staphylococcus aureus, mould and yeast counts were found 4.5 × 103 cfu/g, 3.1 × 101 cfu/g, 3.5 × 101 cfu/g, 1.6 × 101 cfu/g, 7.1 × 101 cfu/g and 8.1 × 101 cfu/g at wheat samples, respectively. While coliform, B.cereus, S. aureus, mould and yeast rates were detected 37.04, 18.52, 22.22, 40.74 and 37.04 %, respectively; in none of the samples, Salmonella spp., Escherichia coli and Clostridium perfringes were not determined. Dry matter, moisture, protein and ash means in wheat samples were calculated as 92.38, 7.62, 11.30 and 1.65 %. It was seen that the quality of wheat cultivars might change regarding production, storage, climate and other regional conditions. It is thought that it would be possible to get quality and healthy product with good production and protection techniques in all stages from harvest to the last product.